The Muara: A Living River Lab in Muar (English Version) - Abd Rahman, Nur Hidayah; Nopiah, Julaina; Suhaimi, Mohamad Suhaizi; Ramdzan Ali, Al Amirul Eimer; Razali, Khairil Azwar (Kulliyyah of Languages and Management, 2021)
This coffee table book is a compilation of successful stories on the transformative teaching and learning at the Kulliyyah of Languages and Management, IIUM. The transformations have been made successful through the flagship project initiative as a platform to contribute to the society by looking into the problems and issues that are related to the social, economy and the environment in Muar. This flagship project started in August 2018, and it has been listed as one of the flagship project initiatives in the IIUM Roadmap 2019-2020. This project has successfully integrated into nine (9) courses and utilised the undergraduate research through Final Year Project which involved Department of Tourism (DOT), Department of Malay (DOM), and Department of English (DOE). This flagship project has published various research publications through successful research grants and won several innovation awards. There are various community engagement programmes that have been conducted through this flagship project platform since the inception of the project. The novelty of The Muara flagship project is through various aspects from the transformative teaching and learning which involves different disciplines, research and publication, the collaboration of inter-kulliyyah and external collaboration, and the community engagement programmes. This project shows its uniqueness in achieving the Sustainable Development Goals, strategic collaboration through the shared platform and harmonising the Maqasid Syariah based on the activities and programmes that have been conducted. This project is a continuous effort to benefit the local people and IIUM community in achieving sustainability in terms of its social, economy and environment.